El clásico Madrid-Barça: own and joint management the exploitation of audiovisual rights in the television broadcasting (1959-2022) - Balsalobre Muñoz, Gonzalo; García González, Isabel Mª (Revista General de Información y Documentación, 2023)
Clashes between Real Madrid and FC Barcelona are among the most followed sport events on television in the world. This study provides a historycal approach to the exploitation of broadcasting rights in Spain, of one of the most rivalry in the world and the audiovisual management of these two clubs, through the importance of this phenomenon with contextual exploration of informative publications and documentary analysis. El clásico has been leading to a transformation in the television commercialization for decades from its origin with the essential interest of 1959 till the current varieties of marketing strategies the star sport event of the Spanish media industry.